Ludwik Fleck - outsider, prekursor, klasyk? = Ludwick Fleck - an outsider, a forerunner, a classic? - Bytniewski, Paweł (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The sociology of knowledge is a field of study with a rather blurry disciplinary standing. Its epistemological status (science or meta-science?), disciplinary affiliation (philosophy or sociology?), and even its history (who was the first, more important, etc: Mannheim, Znaniecki, Scheler?) remain vague.
Keywords: Fleck, Ludwik (1896-1961); socjologia wiedzy